2021
DOI: 10.3389/fevo.2021.569741
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Weather on Avian Growth and Implications for Adaptation to Climate Change

Abstract: Climate change is forecasted to generate a range of evolutionary changes and plastic responses. One important aspect of avian responses to climate change is how weather conditions may change nestling growth and development. Early life growth is sensitive to environmental effects and can potentially have long-lasting effects on adult phenotypes and fitness. A detailed understanding of both how and when weather conditions affect the entire growth trajectory of a nestling may help predict population changes in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 226 publications
(236 reference statements)
4
48
1
Order By: Relevance
“…Physiological and life history traits that impact fitness can be influenced by environmental conditions, in particular temperature, experienced during early life stages (Lindström, 1999;Monaghan, 2008;Conradie et al, 2019). Exposure to high temperature can elicit stress responses (Boddicker et al, 2014), alter metabolism (O'Steen and Janzen, 1999;Moraes et al, 2003;Schnurr et al, 2014), modify water balance (Williams and Tieleman, 2000;McWhorter et al, 2018), impact growth and body size (O'Steen, 1998;Andrew et al, 2017;Andreasson et al, 2018;Sauve et al, 2021), and disrupt functional processes at the subcellular level (Paital and Chainy, 2014). Understanding the physiological impacts of high temperature is particularly important considering that anthropogenic climate change is resulting in an increase in the duration, frequency, and intensity of heat waves (Meehl and Tebaldi, 2004;Tebaldi et al, 2006;Pachauri et al, 2014;Conradie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological and life history traits that impact fitness can be influenced by environmental conditions, in particular temperature, experienced during early life stages (Lindström, 1999;Monaghan, 2008;Conradie et al, 2019). Exposure to high temperature can elicit stress responses (Boddicker et al, 2014), alter metabolism (O'Steen and Janzen, 1999;Moraes et al, 2003;Schnurr et al, 2014), modify water balance (Williams and Tieleman, 2000;McWhorter et al, 2018), impact growth and body size (O'Steen, 1998;Andrew et al, 2017;Andreasson et al, 2018;Sauve et al, 2021), and disrupt functional processes at the subcellular level (Paital and Chainy, 2014). Understanding the physiological impacts of high temperature is particularly important considering that anthropogenic climate change is resulting in an increase in the duration, frequency, and intensity of heat waves (Meehl and Tebaldi, 2004;Tebaldi et al, 2006;Pachauri et al, 2014;Conradie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Growth rate is known to be influenced in a complex manner by weather conditions [34], and previous experimental studies increasing nest temperature have reported contrasted results (positive effect: [17]; negative effects: [10,18]). Our experimental manipulation did not affect body size or mass during postnatal growth, but our results suggest that intermediate nest temperature might be optimal in our great tit population (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…weather) conditions surrounding the nest influence offspring nest-space use. Specifically, two important environmental factors, weather and predation risk (Lima 2009;Chalfoun and Martin 2010;Rivrud et al 2010;Reichert et al 2012;Sauve et al 2021), seem to affect the trade-off nestlings face when choosing between the two preferred localities in the nest. Given the relatively long developmental period of hoopoe nestlings (Krištín 2001;Hudec and Šťastný 2005) and the fact that they are still immature and clumsy when the recordings were made, it is surprising to observe nestlings actively responding to environmental changes with differential nest-space use.…”
Section: Discussionmentioning
confidence: 99%
“…Weather and predation risk are important environmental factors that may be difficult to forecast, at least in specific landscapes and climatic regions (Lima 2009;Chalfoun and Martin 2010;Rivrud et al 2010;Reichert et al 2012;Sauve et al 2021). Thus, when choosing a habitat, animals have to cope with more or less unpredictable environmental conditions throughout their whole life and adjust their life history traits to changes in the environment (Tökölyi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation